Merger waves: the effect on post-merger corporate Pperformance - Ivackovic, Sara (2022)
The research offers a thorough analysis of the influence of historical merger waves on post merger corporate performance. Through the application of statistical tests and regressions, I show that mergers and acquisitions initiated during merger waves are associated with higher short-term abnormal stock returns and lower long-term abnormal stock returns. In contrast to existing research, I use the Fama–French three-factor model to measure the cumulative abnormal stock performance of acquirers for two-day, two-year, and three-year periods following the acquisition.